Menyeimbangkan Model 4C dalam Pemasaran Media Sosial: Analisis Isi Strategi Brand Awareness pada Industri Air Minum dalam Kemasan di Instagram - Cantika Putri, Afisa; Fikrani Deslia, Iva (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2026)
Competition in the bottled drinking water industry requires companies to optimize effective marketing communication strategies in building brand awareness through social media. Although Instagram is widely used as a digital marketing platform, studies examining the implementation of social media marketing using the 4C mode in the context of the AMDK industry remain limited. Furthermore, few studies have analyzed in depth the balance among digital communication strategy dimensions in shaping brand awareness. This study aims to analyze Aquviva’s social media marketing strategy in building brand awareness based on the 4C model, which consist of context, communication, collaboration, dan connection. This research employs a qualitative approach using content analysis of Aquviva’s Instagram posts. The data were analyzed by classifying contont according to indicators within each dimension of the 4C model. The results indicate that the context and communication dimensions are the most dominant aspects of Aquviva’s communication strategy, as reflected in the consistent presentation of educational, health, and lifestyle content, as well as active audience engagement through interactive features. In contrast, the collaboration and connection dimensions remain relatively weak duet o limited strategic partnerships with external parties and suboptimal efforts to build long-term relationships with followers. This condition suggest that Aquviva’s strategy focuses more on message delivery and short term interaction than on strengthening audience loyalty. Theoretically, this study reinforces the relevance of the 4C model in analyzing social media marketing in the AMDK industry. Practically, the findings rovide references for companies in designing more balanced and sustainable digital communcation strategies.